Синтез и свойства микро/мезопористых материалов в тройной системе TiO₂–Al₂O₃–SiO₂ - Хоменко, К.Н.; Редькина, А.В.; Оранская, Е.И.; Цыба, Н.Н. (Поверхность, 2008)
Предложен метод одностадийного синтеза Ti- и Al-содержащих мезопористых молекулярных сит (Ti,Al-MМС) и мезопористых цеолитов (Ti, Al-MZ), исследована кинетика их образования и структурно-текстурные свойства. Полученные материалы охарактеризованы методами ИК-спектроскопии, рентгенографии и адсорбции азота. Показано, что образование цеолитных структур (до ~ 25 %) не сопровождается разрушением мезофазной структуры и происходит в стенках мезопор. Тестирование полученных материалов как катализаторов в реакциях дегидрирования (ДГ) и окислительного дегидрирования пропана в пропилен показало их высокую селективность (~ 75 %) в реакции дегидрирования при выходе пропилена 33 %. A method of one-stage synthesis of Ti- and Al-containing moleculer sieves (Ti, Al-MMS) and mesoporous zeolites (Ti, Al-MZ) containing materials based on has been proposed; the kinetics of their formation and texture features has been studied. The materials obtained have been characterized by methods of IR-spectroscopy (FTIR), X-ray diffraction (XRD), and adsorption of nitrogen. The formation of zeolite structures (up to ~ 25 %) has been shown to be accompanied with destruction of mesophase structure but to occurr in the mesopore walls. Testing the materials obtained as catalysts in the reaction of dehydration and oxidative dehydrogentation of propane into propylene has shown a high selectivity (~ 75 %) in the dehydration reaction with yield of propylene about 33 %.